Unraveling the effects of polychronic orientation and distributive justice on turnover intention: The mediating role of job satisfaction - Gorda, Anak Agung Ngurah Eddy Supriyadinata; Subrata, I Wayan Wisnu; Saputra, I Gusti Ngurah Widya Hadi; Jamil, Nor Suhaira; Singh, Sanju Kumar; Gautama, Anak Agung Ngurah Restu; Wardani , Kadek Devi Kalfika Anggria (Jurnal Fokus Manajemen Bisnis, 2025)
Employee turnover remains a significant concern in the competitive retail market, necessitating a thorough examination of its underlying causes. The present research explores how polychronic orientation and distributive justice affects turnover intention, with job satisfaction as mediators. Data from 100 frontline retail personnel were analyzed using a quantitative methodology, and correlations were assessed through Partial Least Squares Structural Equation Modelling. The findings from studies demonstrate that polychronic orientation markedly enhances distributive justice and turnover intention. Yet, its positive effect on job satisfaction lacks statistical significance. Distributive justice has a little impact on job satisfaction but exerts a significant influence on turnover intention. Job satisfaction significantly and positively affects turnover intention. Mediation analysis reveals that job satisfaction does not significantly mediate the relationships between distributive justice and turnover intention, nor between polychronic orientation and turnover intention. From a Person-Job Fit perspective, his suggests that alignment between individual preferences and job characteristics alone may not reduce turnover intention without supportive organizational conditions. Mediation analysis reveals that job satisfaction does not significantly mediate the relationships between distributive justice and turnover intention nor between polychronic orientation and turnover intention, underscoring the complex interplay of fairness perceptions and individual-job fit in shaping turnover. These findings emphasize the need for organizations to consider both individual traits and justice perceptions within their structural and cultural frameworks to effectively manage employee retention.